Origin and evolutionary dynamics of Hepatitis B virus (HBV) genotype E in Madagascar. (2nd January 2017) - Lo Presti, Alessandra; Andriamandimby, Soa Fy; Lai, Alessia; Angeletti, Silvia; Cella, Eleonora; Mottini, Giovanni; Guarino, Michele Pier Luca; Balotta, Claudia; Galli, Massimo; Heraud, Jean-Michel; Zehender, Gianguglielmo; Ciccozzi, Massimo
Abstract: Africa is one of the endemic regions of HBV infection. In particular, genotype E is highly endemic in most of sub-Saharan Africa such as West African countries where it represents more than 90% of total infections. Madagascar, which is classified as a high endemic area for HBV and where the most prevalent genotype is E, might play a relevant role in the dispersion of this genotype due to its crucial position in the Indian Ocean. The aim of this study was to investigate the origin, population dynamics, and circulation of HBV-E genotype in Madagascar through high-resolution phylogenetic and phylodynamic approaches. The phylogenetic tree indicated that Malagasy isolates were intermixed and closely related with sequences mostly from West African countries. The Bayesian tree highlighted three statistically supported clusters of Malagasy strains which dated back to the years 1981 (95% HPD: 1971–1992), 1986 (95% HPD: 1974–1996), and 1989 (95% HPD: 1974–2001). Population dynamics analysis showed an exponential increase in the number of HBV-E infections approximately from the year 1975 until 2000s. The migration analysis was also performed and a dynamic pattern of gene flow was identified. In conclusion, this study confirms previous observation of HBV-E circulation in Africa and expands these findings at Madagascar demonstrating its recent introduction, and highlighting the role of the African countries in the spread of HBV-E genotype. Further studies on molecular epidemiology of HBV genotype E are needed to clarify the evolutionary history of this genotype.